IMPLEMENTATION OF CHILD-FRIENDLY REGENCY REGULATION IN PREVENTING CHILD SEXUAL VIOLENCE - Chostansia Ketti; Ajis Salim Adang Djaha; Riswanda Riswanda (DIA: Jurnal Administrasi Publik, 2026)
Child protection is a strategic issue in human development, yet cases of child sexual violence continue to rise despite the existence of regulatory frameworks. This study aims to analyze the implementation of Regional Regulation Number 10 of 2022 concerning the Implementation of Child-Friendly Regencies (KLA) in preventing child sexual violence in Sabu Raijua Regency. Utilizing a qualitative case study approach, data is collected through in-depth interviews, non-participatory observation, and documentation involving 25-35 informants selected via purposive and snowball sampling. The results highlight a significant gap between normative policy objectives and empirical reality, influenced by resource limitations, weak cross-sectoral coordination, and the dominance of customary dispute resolution mechanisms over formal legal processes. It is concluded that the effectiveness of the KLA policy relies heavily on balancing the policy content with the local socio-cultural implementation context, requiring strategic capacity building and community literacy enhancements to ensure comprehensive child protection